Cooperative Assembly of Hydrogen-Bonded Diblock Copolythiophene/Fullerene Blends for Photovoltaic Devices with Well-Defined Morphologies and Enhanced Stability - Lin, Ying; Lim, Jung Ah; Wei, Qingshuo; Mannsfeld, Stefan C. B.; Briseno, Alejandro L.; Watkins, James J. (AMER CHEMICAL SOC, 2012)
We report the cooperative self-assembly of functionalized fullerenes and all conjugated block copolymers (BCPs) containing polythiophene derivatives in both segments to yield solar cells with well-defined nanostructures and enhanced morphological stability. Favorable hydrogen bonding interactions between the COOH-functionalized fullerene, bis-[6, 6]-phenyl C61-butyric acid (bis-PCBA), and the tetraethyleneglycol side chains of poly(3-hexylthiophene)-block-poly[3-(2,5,8,11-tetraoxadodecane)thiophene] (P3HT-b-P3TODT) allows for high loading of bis-PCBA (up to 40 wt % to the blend) within the P3TODT domains, while preserving the lamellar morphology. Characterization by grazing incidence small-angle X-ray scattering, electron microscopy, and atomic force microscopy indicates that the periods of the structures range between 24 and 29 nm depending on the bis-PCBA loading. The hydrogen bond interactions between bis-PCBA and P3TODT segments further suppress crystallization and macrophase separation of the fullerenes, even under harsh annealing conditions (150 degrees C for 12 h). Bulk heterojunction solar cells prepared using P3HT-b-P3TODT/bis-PCBA exhibit a photoconversion efficiency of 2.04%, which is greater than that of a reference system, P3HT-b-P3TODT/bis-PCBM. Accelerated aging experiments reveal enhanced thermal stability as a result of the limited translational mobility of COOH-functionalized fullerene in P3HT-b-P3TODT relative to devices prepared using bis-PCBM in P3HT-b-P3TODT or P3HT. We believe that cooperative assembly using strong noncovalent interactions is a general approach that can be used to improve the processing, morphological stability, and aging of organic and hybrid photovoltaic devices.
Keywords: HETEROJUNCTION SOLAR-CELLS; TRIBLOCK COPOLYMER SURFACTANTS; BLOCK-COPOLYMERS; MICROPHASE SEPARATION; REGIOREGULAR POLY(3-HEXYLTHIOPHENE); FULLERENE COMPOSITES; CHARGE-TRANSPORT; SIDE-CHAIN; THIN-FILMS; POLYMER